DESIGN RESEARCH: PENGEMBANGAN PEMBELAJARAN DENGAN PENDEKATAN PMRI PADA MATERI PELUANG UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS BERBUDAYA LOKAL JAKARTA - Kurniawaty, Rina; Makmuri; Meiliasari (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
The results of the preliminary study show that students' mathematical literacy skills on the topic probability was low. This is caused by teachers' conservative teaching methods and students who are not familiar with literacy matters. The presentation of opportunity material is not fully adequate to guide students in learning. This research aims to develop learning designs with a Realistic Mathematic Education (RME) approach with local Jakarta culture on opportunity material using the Gravemeijer and Cobb model which consists of three stages, namely experimental preparation), experimental implementation), and retrospective analysis. The research subject was Health Vocational School Mulia Karya Husada class XI. The learning design in question is a learning path known as Hypothetical Learning Trajectory (HLT). HLT is a learning flow consisting of learning objectives, learning activities, and learning process hypotheses to predict how students think and understanding will develop in the context of learning activities. The research results show that there was an increase in students mathematical literacy abilities.